2022
DOI: 10.1111/cas.15567
|View full text |Cite
|
Sign up to set email alerts
|

TIMP1 promotes cell proliferation and invasion capability of right‐sided colon cancers via the FAK/Akt signaling pathway

Abstract: Although right‐sided colorectal cancer (CRC) shows a worse prognosis than left‐sided CRC, the underlying mechanism remains unclear. We established patient‐derived organoids (PDOs) from left‐ and right‐sided CRCs and directly compared cell proliferation and invasion capability between them. We then analyzed the expression of numerous genes in signal transduction pathways to clarify the mechanism of the differential prognosis. Cell proliferation activity and invasion capability in right‐sided cancer PDOs were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…However, further study is required since no increase in MUC1 expression has been reported in animal trials. TIMP1 has been identified as a key contender in colorectal cancer promotion associated with UC (45). TIMP1, an inducible form, is a member of a four-member glycoprotein family that mediates extracellular matrix turnover (46).…”
Section: Discussionmentioning
confidence: 99%
“…However, further study is required since no increase in MUC1 expression has been reported in animal trials. TIMP1 has been identified as a key contender in colorectal cancer promotion associated with UC (45). TIMP1, an inducible form, is a member of a four-member glycoprotein family that mediates extracellular matrix turnover (46).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the effective usage of Timp1-targeted constructions, such as siRNA and shRNA, for the treatment of liver fibrosis [ 104 , 118 ] and other diseases accompanied by an imbalance in the synthesis/degradation of ECM components, such as keloids, was shown [ 119 ]. Additionally, Timp1 knockdown decreases proliferation, migration and invasion of tumor cells of diverse origins [ 120 , 121 , 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…TIMP1 belongs to the TIMP gene family, and encodes a natural inhibitor of MMP. It has been demonstrated that TIMP1 promotes the development of pancreatic cancer, CRC, lung cancer, and gastric cancer (24)(25)(26)(27). It has been reported that overexpression of TIMP1 is associated with poor prognosis and activates the focal adhesion kinase/protein kinase B (FAK/AKT) signaling pathway to promote the proliferation and invasiveness of CRC cells (25,28).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that TIMP1 promotes the development of pancreatic cancer, CRC, lung cancer, and gastric cancer (24)(25)(26)(27). It has been reported that overexpression of TIMP1 is associated with poor prognosis and activates the focal adhesion kinase/protein kinase B (FAK/AKT) signaling pathway to promote the proliferation and invasiveness of CRC cells (25,28). MMP10 belongs to the MMP family, and is a key target of the protein kinase C iota/partitioning defective protein-6 alpha/ras-related C3 botulinum toxin substrate 1 (PKCι/Par6α/Rac1) axis.…”
Section: Discussionmentioning
confidence: 99%